2017
DOI: 10.1175/bams-d-17-0106.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Research Strategy to Better Understand, Observe, and Simulate Urban Atmospheric Processes at Kilometer to Subkilometer Scales

Abstract: di saBatino, JunXia dou, daniel r. dreW, John M. edWards, JoaChiM fallMann, krzysztof fortuniak, JeMMa gornall, toBias groneMeier, Christos h. halios, denise hertWig, kohin hirano, alBert a. M. holtslag, zhiWen luo, gerald Mills, Makoto nakayoshi, kathy Pain, k. heinke sChlünzen, stefan sMith, lionel soulhaC, gert-Jan steeneveld, ting sun, natalie e theeuWes, david thoMson, JaMes a. voogt, helen C. Ward, zheng-tong Xie, and Jian zhong W ith the majority of people experiencing weather in urban areas, it is crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 2 publications
0
33
0
Order By: Relevance
“…Yang et al 2010;Yang and Li 2015), and pollutant dispersion and street-canyon ventilation (Brixey et al 2009;Heist et al 2009;Fuka et al 2018). All of these aspects challenge the general applicability of current urban-modelling concepts in high-rise cities at the local scale and mesoscale (Barlow et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 2010;Yang and Li 2015), and pollutant dispersion and street-canyon ventilation (Brixey et al 2009;Heist et al 2009;Fuka et al 2018). All of these aspects challenge the general applicability of current urban-modelling concepts in high-rise cities at the local scale and mesoscale (Barlow et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly there is the problem of the best way to represent the urban surface (Best and Grimmond, 2015). Barlow et al (2017) identified the main problems as being heterogeneity on many scales, and anthropogenic effects. Models at 100 m scales will have to operate between the traditional convection-permitting NWP regime where there are many buildings per grid box and the very high-resolution regime of LES modelling of individual buildings and streets (the so-called "building grey zone").…”
mentioning
confidence: 99%
“…Developing methods to emulate the dynamics of human behaviour therefore is essential so that spatially heterogeneous Q F predictions can be made (Barlow et al 2017). In turn, this will support urban energy balance and surface-atmosphere interaction modelling at progressively higher spatial and temporal resolutions.…”
Section: Discussionmentioning
confidence: 99%